DECODING THE DYNAMICS IN FINANCIAL FRAUD - Adiningsih, Triana Eva (Jurnal Akuntansi dan Keuangan Indonesia, 2024)
This empirical study examines fraud for the entire period and then compares it with the latest trends in the five years. This study utilizes extensive data sets to analyze specific aspects of fraud, including causes, types, solutions, and real-world cases. This study conducted a systematic literature review of relevant literature by taking data from Scopus-indexed journals. Vosviewer was used to identify events, and spreadsheet file information was grouped manually. Interestingly, the cheating types of ‘five-year statistics’ and ‘all-time statistics’ show slightly different frequencies. The main research topics focus on money laundering and financial crimes. To explore this further, this report compares historical publications on fraud with current publications, highlighting relevant information from recent articles. The findings of this study have practical implications for understanding and combating fraud in the real world.